Novel blind audio watermarking algorithm in the hybrid domain - WANG Xiang-yang1; YANG Hong-ying1; NIU Pan-pan1 (Tongxin xuebao)
A new robust digital audio watermarking against desynchronization attack using DWT and DCT was proposed.Firstly,the origin digital audio was segmented and then each segment was cut into two sections.Secondly,with the spa-tial watermarking technique,synchronization code was embedded into the first section.Finally,the DWT and DCT were performed on the second section,and then the watermark was embedded into the low frequency components by quantiza-tion.Experiment results show that the proposed watermarking scheme is inaudible and robust against various signal processing such as noise adding,re-sampling,re-quantization,random cropping,MPEG audio layer 3（MP3） compression,time-scale modification,frequency-scale modification.